Securing Digital Transactions: The Role of Identity Verification in Reducing E-Commerce Fraud (Journal of Artificial Intelligence Research, 2023)
The exponential growth of e-commerce has revolutionized how transactions are conducted, offering unprecedented convenience and global reach. However, this transformation has also attracted sophisticated cyber threats, including identity theft, account takeovers, and phishing scams, resulting in significant financial and reputational losses. Mobile identity verification has emerged as a pivotal solution, leveraging technologies such as biometrics, multi-factor authentication (MFA), and AI-driven analytics to combat fraud effectively. This paper explores the role of mobile identity verification in enhancing the security of digital transactions in e-commerce. Through a review of recent advancements, case studies, and data analysis, we demonstrate how mobile verification systems reduce fraud, foster consumer trust, and streamline compliance with regulatory frameworks. Despite its efficacy, challenges such as usability concerns, cost barriers, and technical vulnerabilities persist. We propose innovative solutions, including the integration of blockchain technology and advanced behavioral analytics, to address these limitations and outline future research directions for optimizing transaction security in the digital age.
Keywords: Mobile identity verification; e-commerce fraud; digital transaction security; biometrics; multi-factor authentication